Mechanical Ventilation. Total Eclipse of the Heart (Editorial) - G. Landoni; P. Nardelli; A. Zangrillo; L. A. Hajjar (Общая реаниматология, 2021)
Results from recent large randomized trials investigating the use of high PEEP in patients without ARDS all suggest that high levels may increase mortality due to hypotension and bradycardia. A careful assessment of cardiac function — with particular focus on the right ventricle — should be performed before planning our ventilation strategy in any setting, including COVID-19 and ARDS in general. Mechanical ventilation should be respectful in regards of heart function, and tolerant with moderate hypoxia and hypercapnia, noninvasive (whenever possible) and synchronized.